Blood Flow Modelling to Improve Cardiovascular Diagnostics: a Preliminary Review of 1-D Modelling - Butt, A.; A. Abakr, Y.; B. Mustapha, K. (International Journal of Engineering and Technology, 2018)
Cardiovascular diseases issue an enormous threat to the health and general wellbeing of the population, therefore multidisciplinary knowledge of the cardiovascular system and its mechanics has become a necessity. Due to the lack of wide scale experimental studies, the limitations associated with it and the immense advances in computational technology, in recent years, numerical modelling of the cardiovascular system has gained popularity as a viable alternative. One-dimensional models as compared to higher dimensional models provide a feasible and efficient means to study the dynamics of pulse wave propagation in order to increase the comprehension of circulatory physiology. The aim of this paper is to provide an overall review of the types, solution methods, treatment of boundary conditions, applications and advantages as well as disadvantages of one-dimensional models of the human arterial network.Â Â